Enseñanza aprendizaje de la geometría plana a través de un holograma - Gualan Macas, Ericka Nancy (2025)
The hologram as a didactic material is a useful tool that facilitates the didactic process of plane geometry through the manipulation and three-dimensional visualization of geometric figures in a realistic way. The objective of this research was to enhance the teaching and learning process of plane geometry through the development of an innovative resource. A mixed non-experimental approach with descriptive scope, inductive-deductive method was considered, being survey and interview employed techniques. A hologram was developed, classes were given and the level of satisfaction of a given group of students was measured. As a result of the research, a great level of satisfaction among students is highlighted, who showed greater attention, motivating them to curiosity for better learning, as reflected in the survey conducted at the end of the implementation. In conclusion, it is observed that the hologram as a didactic material encourages active participation and creates a new learning environment